Implementation of technology innovation in MSMEs in India: Case study in select firms from Northern region. Issue 3 (3rd September 2019) - Singh, Davinder
Abstract : Purpose: In the present age of globalization, micro, small and medium enterprises (MSMEs) are consistently causative to productivity growth and, consequently, competitiveness and aggregate economic growth by providing the training opportunities, basic services and are believed to be especially effective job creators and enjoy the reputation of being sources of income. But technological progressions have increased greatly, the competition impelled by the globalization of the world economies and even MSMEs are no more protected to the challenges that the globalization brings about. It is a remarkable, and in certain instances, a worrying situation because MSMEs play an important role in most economies, including in India, in that they comprise the largest business block and offer the bulk of employment. The purpose of this paper is to assess the status of problems faced by MSMEs and study the technology innovation implementation (TII) dimensions in the selected small firms in the Northern region in India. Design/methodology/approach: The methodology used for this study is a combination of literature review, expert opinion, comparative case study and a flexible systems methodology, SWOT and situation-actor-process-learning-action-performance analysis. Longitudinal studies of technology innovation at the two small firms have been conducted, and the case analysis and synthesis have been developed based on important inputs and insights shared by key personnel in the select firms. Findings: The study finds that two different firms have faced similar kind of challenges in this competitive environment. Also the findings suggest that an effective TII can contribute to enhance manufacturing performance in MSMEs in India. Originality/value: The research presents a better understanding of the problems that are preventing the successful implementation of technology innovation in small firms. Further, the two cases provide valuable insights into TII dimensions in two firms and highlight the methodology to be adopted by the companies toward their manufacturing performance enhancement.